Exclusive 6 month-breastfeeding and associated factors among healthy newborns - Cairo Lavado, Javier (2000)
OBJECTIVES: To determine if factors such as maternal characteristics, hospital procedures and neonatal weight loss, were related to exclusive breastfeeding (EBF) up to 6 months among healthy newborns at the Navy Medical Center (NMC) in 1998. MATERIALS AND METHODS: Clinical histories of infants born in 1998 were reviewed, and was assessed the existence of a relationship between the up-to-6-month EBF and mother's parity and age, military rank of the navy member relative, infant gender, neonatal weight loss and hospital glucose-based solution and mother milk substitutes giving. RESULTS: Up to 6 month age 36,7% of studied population (40/109) were on EBE CONCLUSIONS: Mother's relative military rank and non-use of the preparation supplements during neonatal period were the factors associated with 6-month lasting EBE.